Analisis Ekuitas Merk Brand Loyalty Terhadap Keputusan Pembelian Teh Botol Sosro Pada Mahasiswa Universitas Bina Sarana Informatika Kampus Pemuda - Chanissa Purwaningrum (Penerbit Jurnal Indonesia, 2026)
This study aims to analyze the effect of brand equity, particularly brand loyalty, on the purchasing decisions of Teh Botol Sosro among students of Universitas Bina Sarana Informatika, Pemuda Campus. Brand equity is an important factor in marketing strategy that influences consumer perceptions, preferences, and purchasing behavior. Brand loyalty reflects consumers’ commitment to repurchase a product consistently and to recommend it to others. This study applied a quantitative method, with data gathered by distributing questionnaires to students as respondents. Data analysis techniques included validity and reliability tests, simple linear regression analysis, and hypothesis testing to determine the extent of the influence of brand loyalty on purchasing decisions. The findings show that brand loyalty exerts a positive and statistically significant influence on purchasing decisions.The higher the level of student loyalty toward the brand, the greater their tendency to repurchase the product. This study is expected to provide valuable insights for companies in maintaining and enhancing consumer loyalty, particularly among university students, through appropriate and sustainable marketing strategies.